Unraveling the Toxicity of a Non-Microcystin-Producing Strain (CCIBt3106) of Microcystis aeruginosa: Ecotoxicological Effects on Aquatic Invertebrates - Éryka Costa Almeida; Fernanda Rios Jacinavicius; Rhuana Valdetário Médice; Rafaella Bizo Menezes; Larissa Souza Passos; Dominique Anderson; Jaewon Yoon; Elaine Dias Faria; Camila Manoel Crnkovic; Ana Lúcia Fonseca; Theodore Henry; Ernani Pinto (Toxins)
Cyanobacterial blooms are becoming increasingly frequent and intense worldwide, often dominated by Microcystis aeruginosa, a species capable of producing a wide array of bioactive metabolites beyond microcystins. This study evaluates the ecotoxicological potential of a non-microcystin-producing strain, M. aeruginosa CCIBt3106, using acute immobilization assays with three microcrustacean species: Daphnia similis, Artemia salina, and Parhyale hawaiensis. Biomass was extracted using solvents of varying polarity, and selected extracts (aqueous and 50% methanol) were further fractionated and analyzed via high-resolution liquid chromatography–tandem mass spectrometry (HR-LC-MS/MS). Significant toxicity was observed in D. similis and P. hawaiensis, with EC50 values ranging from 660 to 940 µg mL−1. Metabolomic profiling revealed the presence of chemically diverse metabolite classes, including peptides, polyketides, and fatty acyls, with putative annotations linked to known bioactivities. These findings demonstrate that cyanobacterial strains lacking microcystins can still produce complex metabolite mixtures capable of inducing species-specific toxic effects under environmentally relevant exposure levels. Overall, the results highlight the need to expand ecotoxicological assessments and monitoring frameworks to include non-microcystin cyanobacterial metabolites and strains in water quality management.